(untitled) (Bangladesh Journal of Agricultural Research, 2010)
The effect of two planting methods (direct seed sowing and transplanting of seedlings) and seven dates of planting (8 Oct., 2 Nov., 27 Nov., 22 Dec., 16 Jan., 10 Feb. and 5 March) on the production of lettuce was compared. ‘Green Wave’ a loose leaf Japanese variety was used. The average yield of the direct seeded crops (17.16 t/ha) was found to be almost double than that of the transplanted crops (9.08). The yields (t/ha) from different dates of planting were 13.7 (8 Oct.), 15.04 (2 Nov.), 8.94 (27 Nov.), 14.54 (22 Dec.), 21.45 ( 16 Jan.) 10.16 (10 Feb.), and 8.02 (5 March). The highest yield of 24.0 t/ha was obtained from direct seedling on 16 January. Key Words: Method; date; planting; production of lettuce. DOI: 10.3329/bjar.v34i1.5756 Bangladesh J. Agril. Res. 34(1) : 75-80, March 2009